1994
DOI: 10.1136/gut.35.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori and its eradication on gastric juice ascorbic acid.

Abstract: The presence of ascorbic acid in gastric juice may protect against gastric carcinoma and peptic ulceration. This study examined the effect of Helicobacter pylon (H pylon) on the secretion of ascorbic acid into gastric juice by measuring fasting plasma and gastric juice ascorbic acid concentrations in patients with and without the infection and also before and after its eradication. Gastric juice ascorbic acid concentrations in 19 H pylon positive patients were significantly lower (median 2*8, range 0-28*8 [ig/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 27 publications
7
110
1
5
Order By: Relevance
“…It has been clarified that H. pylori induces inflammation in the gastric mucosa, not only by clinical studies showing that the concentration of vitamin C in the gastric juice of the H. pyloriinfected patient was low (20) and the amount of 8-oxodG, a biomarker of oxidative stress, of the gastric mucosa of the H. pylori infected patient was high (21), but also by animal data showing that H. pylori induced IL-8 production by gastric mucosal epithelial cells (22). Antioxidative substances have been expected to suppress inflammation, because the reactive oxygen species is related to the improvement of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clarified that H. pylori induces inflammation in the gastric mucosa, not only by clinical studies showing that the concentration of vitamin C in the gastric juice of the H. pyloriinfected patient was low (20) and the amount of 8-oxodG, a biomarker of oxidative stress, of the gastric mucosa of the H. pylori infected patient was high (21), but also by animal data showing that H. pylori induced IL-8 production by gastric mucosal epithelial cells (22). Antioxidative substances have been expected to suppress inflammation, because the reactive oxygen species is related to the improvement of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Low intake of other nutrients such as ®ber, ascorbic acid and alcohol in patients with endoscopically veri®ed ulcer compared to controls has been reported by previous studies and similar to our results (Mullan et al, 1994). The possible protection of ascorbic acid in gastric juice against peptic ulceration and gastric carcinoma has been investigated (Banerjee et al, 1994). Studies have suggested that vitamin C protects against H. pylori infection (Nilius et al, 1991;Goodman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic gastritis is associated with excessive production of reactive oxygen metabolites and H. pylori infection is also associated with decreased intragastric ascorbic acid levels, a critical antioxidant. 20 H. pylori causes increased mucosal proliferation. 21,22 Increased cell proliferation is associated with an increased risk of somatic mutations due to replication errors and inadequate DNA repair.…”
Section: Pathogenesis Of Gastric Cancermentioning
confidence: 99%